2016
DOI: 10.1097/pcc.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Intensive Care Society 2014 Consensus Statement

Abstract: In the cardiac ICU, management of the cardiac patient requires an individualized sedative and analgesic strategy that maintains hemodynamic stability. Multiple pharmacological therapies exist to achieve these goals and should be selected based on the patient's underlying physiology, hemodynamic vulnerabilities, desired level of sedation and analgesia, and the projected short- or long-term recovery trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…In our experience, the use of medications that lower the vascular tone and resistance were associated with severe cyanosis and shunt thrombosis. 8 9 15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experience, the use of medications that lower the vascular tone and resistance were associated with severe cyanosis and shunt thrombosis. 8 9 15…”
Section: Resultsmentioning
confidence: 99%
“…Some sedatives have similar effects to prostaglandins on the systemic and pulmonary circulation and should be avoided. 8 9 15 In such cases, we recommend initiation of alpha agonists (phenylephrine) concomitantly with prostaglandin E1 and prior to initiation of sedation.…”
Section: Resultsmentioning
confidence: 99%
“… 7 8 The recent consensus statement by Lucas et al describes the pharmacotherapies currently available to manage pain and sedation in paediatric cardiac critical care patients and summarises dosing recommendations from available literature. 13 Lucas and colleagues conclude that a more individualised analgesic and sedative treatment strategy is necessary to provide optimal care without adverse effects resulting from pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Lucas et al 13 on pharmacotherapies in paediatric cardiac critical care provides an extensive overview of PK of analgesic and sedative drugs used in children after cardiac surgery but focused less on their use in protocols for clinical practice. Changes in clearance and volume of distribution (PK) and/or PD due to the use of cardiopulmonary bypass (CPB), disease processes, low cardiac output syndrome, surgical procedure and age may alter optimal way of dosing analgesics and sedatives in children after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…2 Consensus guidelines, at present, acknowledge the lack of high-quality evidence on which to base practice recommendations for sedation. [3][4][5][6][7][8] This lack of evidence has resulted in heterogeneous approaches to management [9][10][11] and widespread off-label sedative use across paediatric intensive care units (PICUs). [12][13][14][15] For example, a recent systematic review 16 found that optimal sedation was only achieved in little over half (57.6%) of the time.…”
Section: Introductionmentioning
confidence: 99%